2017
DOI: 10.1016/j.immuni.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell Help Confers a Cytotoxic T Cell Effector Program Including Coinhibitory Receptor Downregulation and Increased Tissue Invasiveness

Abstract: CD4 T cells optimize the cytotoxic T cell (CTL) response in magnitude and quality, by unknown molecular mechanisms. We here present the transcriptomic changes in CTLs resulting from CD4 T cell help after anti-cancer vaccination or virus infection. The gene expression signatures revealed that CD4 T cell help during priming optimized CTLs in expression of cytotoxic effector molecules and many other functions that ensured efficacy of CTLs throughout their life cycle. Key features included downregulation of PD-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
340
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(368 citation statements)
references
References 40 publications
27
340
1
Order By: Relevance
“…2A). It has been demonstrated that the inclusion of “helper” epitopes in therapeutic cancer vaccines improves the antitumor response by increasing the expansion of CD8 + T cells, as well as reducing their expression of coinhibitory receptors and increasing their migratory potential 77 …”
Section: Help In Therapeutic Contextmentioning
confidence: 99%
“…2A). It has been demonstrated that the inclusion of “helper” epitopes in therapeutic cancer vaccines improves the antitumor response by increasing the expansion of CD8 + T cells, as well as reducing their expression of coinhibitory receptors and increasing their migratory potential 77 …”
Section: Help In Therapeutic Contextmentioning
confidence: 99%
“…We were intrigued by earlier findings that extracellular ISG15 may act as an adjuvant to support the CTL response (34). We aimed to corroborate this and to understand the mechanistic basis, making use of a versatile therapeutic DNA vaccination model in mice (37) that we have well characterized previously (38,41,42). In this model, pDNA is applied on the depilated skin and injected into the epidermis using a tattoo device (Fig.…”
Section: Isg15 Causes Innate Immune Alert In the Skinmentioning
confidence: 99%
“…CD4 T cells also promote the ultimate positioning of memory CD8 T cells in the infected respiratory tract (30). Intriguingly, a recent study provided strong evidence that CD4 T cell “help” is critical for development of effector CD8 T cells that have cytotoxic potential, and express molecules critical for homing and extravasation, all key to protective immunity to influenza (31). In addition to potentiating the protective function of other cells in the antigen-specific adaptive response, CD4 T cell memory also likely plays a role in recruitment of early innate effector cells into the lung (32, 33), promoting a complex array of effector mechanisms that can blunt virus infection and replication (reviewed in (34)).…”
Section: Overview: the Contributions Of Cd4 T Cells To Protection Fromentioning
confidence: 99%